A web-based grocery store management system - Lim, Sean Ong Yuan (2014)
Online Inventory Management System is not a recent development. However, it is still not very widely used and implemented, especially in small scale buisnesses. The main reasons would be the resistance to change and the Iack of technical knowledge. Through careful research, it can be seen that large supermarkets are already adopting an online approach to sales to capture the online market and that there are clear benefits to the implementation of an online web store.